Hydrothermal synthesis and characterization of calcium phosphate-based coatings on AZ31 magnesium alloy - Horáková, L.; Doskočil, L.; Wasserbauer, J.; Buchtík, M. (Korose a ochrana materiálu, 2023)
This study aims to analyze the influence of process parameters used for hydrothermal synthesis of CaP coatings on their properties and to improve their corrosion resistance and biocompatibility compared to the substrat AZ31. The parameters monitored were deposition time, pH of the reaction mixture, and concentration of precursors in the reaction mixture. For the deposited CaP coatings on AZ31 magnesium alloy, the surface morphology and the number of structural defects were evaluated using scanning electron microscopy. Electrochemical corrosion properties were evaluated using polarization techniques in Hank’s solution. The results showed that the best properties were obtained for the sample prepared in a reaction mixture at 120 °C, pH 5 for a deposition time of 120 min, when the concentration of precursors in the reaction mixture was 0.30 mol/l Ca(NO ·4H O and 0.28 mol/l NH PO . Under these conditions, the best electrochemical corrosion properties were achieved.